2002
DOI: 10.3109/j180v01n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Impairments, Disabilities and Life Satisfaction in Patients with Chronic Whiplash Associated Disorders

Abstract: Introduction. The main aims of the present study were: (1) to compare aspects of disability (activity preferences and sick leave) and perceived global situation (life satisfaction) in a patient group with chronic whiplash associated disorders (WAD group; N = 32) with a healthy group of subjects (without neck or shoulder pain) randomly recruited from the official census lists (C group; N = 55), (2) to investigate whether the WAD group has a general hyper vigilance with respect to symptoms and (3) to analyse whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Sterner et al (33) reported that patients with chronic WAD had a significantly higher prevalence of different symptoms than healthy controls, but they also noted that the chronic WAD group did not exhibit a homogenous increase in all types of symptoms. For individual not directly pain-related items (cf .…”
Section: Comparisons Between Subgroups Based On Primentioning
confidence: 99%
See 2 more Smart Citations
“…Sterner et al (33) reported that patients with chronic WAD had a significantly higher prevalence of different symptoms than healthy controls, but they also noted that the chronic WAD group did not exhibit a homogenous increase in all types of symptoms. For individual not directly pain-related items (cf .…”
Section: Comparisons Between Subgroups Based On Primentioning
confidence: 99%
“…Patients with chronic WAD rate their satisfaction with life as a whole (physical and psychological health) lower than healthy controls (33). A prominent majority of the different items and scales concerning life satisfaction and health (i.e.…”
Section: Comparisons Between Subgroups Based On Primentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic pain, including chronic whiplash-associated disorder (WAd), has a negative impact on quality of life (1,2) and negative consequences for perceived health (3)(4)(5). The bio-psychosocial framework of chronic pain (6) proposes an interaction between several factors that influence the development and maintenance of chronic pain and its consequences.…”
Section: Introductionmentioning
confidence: 99%